Karzeł, żaba i obcy, czyli surrealistyczna opowieść o Holokauście - Janik, Gaweł (Narracje o Zagładzie [czasopismo zamknięte], 2015)
The midget, the frog and the stranger or a surreal story about the Holocaust The article attempts to indicate a change in the means of representing the Shoah. The latteri s more and more frequently described with the use of the means suggested by popular culture. An attempt was made to reconstruct the evolution of the discourse of the Shoah, with special reference to the contemporary representations which were discussed on the basis of the example of the comic book genre. The subject of the Holocaust comic book was treated in a comprehensive manner by exploring its history, constitutive features and criticism. The comic book entitled Achtung Zelig! Druga wojna by Krzysztof Gawronkiewicz and Krystian Rosenberg was used as an example to illustrate the problem which is engaged in the article. Special attention was devoted to its genesis, its realisation of the features peculiar to the genre, its innovative nature and reception. There is an indication of the sources of the surreal convention which was employed by the Polish authors. This convention may have originated, among other things, from the occult roots of Nazism. The authors also mentioned the links between Achtung Zelig!… with cinematographic works such as Hanna by Joe Wright and Zelig by Woody Allen, as well as with Krzysztof Zalewski’s musical project of the same title. Moreover, the authors indicated the similarities between Achtung Zelig!… and Maus by Art Spiegelman in an attempt to evaluate the extent to which the employment and transformation of models used in the American graphic novel was successful in the case of the Polish comic book. Key words: Holocaust, Shoah, comic books, popular culture, Achtung Zelig!, Maus